Underwater Acoustic Channel Characterization of Shallow Water Environment - Santoso, Tri Budi; Widjiati, Endang; Wirawan, Wirawan; Hendrantoro, Gamantyo (Politeknik Elektronika Negeri Surabaya (PENS), 2018)
Understanding of channel propagation characteristics is a key to the optimal design of underwater acoustic communication. Generally, modelling of underwater acoustic channel is performed based on measurement result in certain site at certain times. Different sites might have different characteristics, each of which can generally be described by a model obtained by averaging measurement results at multiple points in the same environment. This paper describes a characterization of the underwater acoustic channel of tropical shallow water in a Mangrove estuary, which has sediment up to 60 cm at the bottom. Such a channel model is beneficial for the design of communication system in an autonomous underwater vehicle, for instance. The measurement result of delay spread parameter from three different points with the distance of 14 52 m, has various values. The root mean square (RMS) of delay spread ranges between 0.0621 0.264 ms, and the maximum delay spread varies with the value of 0.187 1.0 ms. The pdf fitting shows that Rayleigh distribution describes the fading variation more accurately than Nakagami and Ricean.